1994
DOI: 10.1017/cbo9780511620690
|View full text |Cite
|
Sign up to set email alerts
|

Input and Interaction in Language Acquisition

Abstract: Language addressed to children, or 'Baby Talk', became the subject of research interest thirty years ago. Since then, the linguistic environment of infants and toddlers has been widely studied. Input and Interaction in Language Acquisition is an up-to-date statement of the facts and controversies surrounding 'Baby Talk', its nature and likely effects. With contributions from leading linguists and psychologists, it explores language acquisition in different cultures and family contexts, in typical and atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…In contrast to other studies that have emphasized fathers' task orientation (Barratt, 1995;Gallaway & Richards, 1994;Henderson, 1991), in the present study fathers' nonverbal behavior was oriented toward solidarity in the collaborative activity. This mapping of the patterns in fathers' interactions with their children is a particular contribution of this study.…”
Section: Task Difficulty Affects Patterns Of Nonverbal Parental Commucontrasting
confidence: 99%
“…In contrast to other studies that have emphasized fathers' task orientation (Barratt, 1995;Gallaway & Richards, 1994;Henderson, 1991), in the present study fathers' nonverbal behavior was oriented toward solidarity in the collaborative activity. This mapping of the patterns in fathers' interactions with their children is a particular contribution of this study.…”
Section: Task Difficulty Affects Patterns Of Nonverbal Parental Commucontrasting
confidence: 99%
“…Complicating the task further, every object is a member of multiple categories that overlap in scope (e.g., grasshopper, bug, insect, animal; green; jumping), yet only a few such categories, if any, will be named in a given encounter. In addition, there is considerable variation, both within and across cultures, in how and how often adults label objects for infants (e.g., Cartmill et al, 2013;Gaskins, 1999;Lieven, 1994;Rogoff, Mistry, Göncü, & Mosier, 1993;Shneidman & Goldin-Meadow, 2012). Finally, even when a caregiver does name an object within the infant's view, identifying the intended referent is often still quite difficult (Cartmill et al, 2013;Gillette, Gleitman, Gleitman, & Lederer, 1999).…”
mentioning
confidence: 99%
“…Many studies propose that CDS in some form exists across all cultures, despite substantial differences in style and frequency of use (Fernald, 1992;Bryant and Barrett, 2007;Saxton, 2009;Piazza et al, 2017). Studies have shown multiple differences between the speech addressed to child and adult interlocutors, providing clear evidence that CDS is a separate speech mode, distinct from ADS (e.g., Snow, 1972;Ferguson, 1978;Ringler, 1981;Gallaway and Richards, 1994;Foulkes et al, 2005). Adults adapt their speech addressed to children in numerous ways including structured repetition (Küntay and Slobin, 1996;Lester et al, 2022), exaggerated articulation (Lindblom, 1990;Minjung and Stoel-Gammon, 2005;Green et al, 2010) and prosody (Fernald and Simon, 1984;McLeod, 1993), syntactic and lexical simplification (Fernald and Morikawa, 1993;Kunert et al, 2011), and a large emphasis on interaction (Hoff and Naigles, 2002).…”
Section: Background and Motivation For The Studymentioning
confidence: 99%
“…In those languages that show evidence of this simplified mode, the simplification affects numerous aspects of caregivers ' speech (e.g., McLeod, 1993;Green et al, 2010;Kunert et al, 2011). Effects in phonology, syntax and the lexicon have been studied extensively in the past decades, demonstrating notable differences between CDS and adult-directed speech (ADS) (e.g., Snow, 1972Snow, , 1995Gallaway and Richards, 1994). When compared to adultdirected speech, CDS is usually slower, has higher pitch and a greater pitch range.…”
Section: Introductionmentioning
confidence: 99%